Configuring Discourses on Black Women’s Power in the Novels, Waiting to Exhale and The Color Purple - Pramono, R.B. Edi; Adi, Ida Rohani; Rokhman, Muh Arif (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2024)
The discourses of the novels, Waiting to Exhale and The Color Purple, show the main characters exercising power in their social power relations, then gaining knowledge, and with knowledge, gaining power. In the former novel, the characters Robin and Bernadine gain knowledge through their relationship with Savannah and Gloria, while in the latter Celie gains knowledge through Nettie’s letters and her intensive acquaintance with Shug. This study thus aimed to analyze how Black women acquire power transformation, and what state of power Black women have before and after this transformation. Our findings showed, first, that they acquire support and help from close friends and families. Second, they gained knowledge and awareness about their positions and weaknesses. And third, they begin determining their wills, passions, and choices. Then, they transform their endurance into power over and power to change from being powerless and submissive into a powerful and self-determining personality. Using Foucault’s theory of power and Foucault’s discourse analysis method, the discourse shows that besides knowledge, self-determination and the supporting milieu are essential factors in gaining power transformation in power relations.